Opportunities for Patient Participation in Perioperative Malnutrition Care: A Qualitative Study - Gerda van den Berg MSc; Marian de van der Schueren PhD; Hester Vermeulen PhD; Getty Huisman-de Waal PhD (SAGE Publishing, 2023)
Introduction In the perioperative period of hospitalization, barriers to food intake are common due to special nutritional needs, compromised nutritional status, and metabolic stress. Good nutritional care call for an interdisciplinary approach. And patients themselves may also play an essential role in managing nutritional care. Objective This study aimed to explore how patients with malnutrition experience nutritional care, their perspectives on patient participation, and their own role in malnutrition care in the perioperative period of hospitalization. Methods A qualitative study was conducted using an interpretive phenomenological approach. To follow patients' experiences, in-depth longitudinal interviews were undertaken before, during, and after hospitalization. Interview transcripts were analyzed thematically using open, axial, and selective coding and interpreted in an iterative process. Results Fifty-six interviews were undertaken with 26 patients with malnutrition scheduled for surgery and during the perioperative period of hospitalization. Four themes were identified: (1) unawareness and stigmata about being malnourished, (2) feasibility of optimal nutritional care, (3) needs and expectations for self-management, and (4) barriers and facilitators of taking own responsibilities in nutritional care. Conclusion Awareness and responsiveness to patients' perspectives, motivation, and compliance are prerequisites for patient participation in malnutrition care. This requires good communication between healthcare professionals and patients in all phases of hospitalization.